Adenosine Receptor 3 in Liver Cancer: Expression Variability, Epigenetic Modulation, and Enhanced Histone Deacetylase Inhibitor Effects - Louise Kaldjob-Heinrich; Sandro Nuciforo; Steffen Lemke; Aaron Stahl; Stefan Czemmel; Sepideh Babaei; Lauriane Blukacz; Marie-Anne Meier; Yizheng Zhang; Christian M. Schürch; Irene Gonzalez-Menendez; Pascal Woelffing; et al. (Gastro Hep Advances)
Background and Aims: Primary liver cancer, including hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), has low response rates to existing treatments, highlighting the urgent need for novel treatment options. Adenosine A3 receptor (ADORA3) signaling has emerged as a potential target. Namodenoson, an ADORA3 agonist, has shown promise in early clinical trials for HCC. However, further data are required to clarify ADORA3 expression patterns in liver cancer, mechanisms of action, and the potential for combination therapies to inform patient selection for future clinical trials. Methods: Patient-derived tissue microarrays and RNA-sequencing were employed to investigate ADORA3 expression. Cellular responses to ADORA3 stimulation and combination treatments were studied in HCC and CCA cell lines and patient-derived organoids (PDOs). Genome-wide RNA-Seq analysis, mRNA analysis, and DigiWest protein profiling were performed. Results: Tissue microarray analysis revealed higher ADORA3 expression in nonmalignant samples and a subset of tumors with weak or absent ADORA3 expression. This was supported by RNA sequencing data from The Cancer Genome Atlas and needle biopsy samples. Cell lines and PDOs exhibited antiproliferative effects with the ADORA3 agonist Namodenoson, confirmed by receptor dependency tests with specific antagonists and siRNA experiments. Genome-wide RNA-Seq analysis suggested chromatin remodeling events after ADORA3 stimulation. mRNA expression and DigiWest profiling identified downregulation of histone deacetylases and histone H3 modifications. Combination treatments with different ADORA3 agonists and histone deacetylase inhibitors significantly enhanced antiproliferative effects in almost all selected combinations, supported by investigations in PDOs. Conclusion: ADORA3 expression varies considerably in HCC or CCA, ranging from high to absent receptor detection. This observation might help to identify patients for clinical studies. Additionally, Namodenoson’s epigenetic modulating activity suggests epigenetic drugs as promising candidates for combination treatment.